MODERN STATE OF APPLICATION OF INFORMATION AND COMMUNICATION TECHNOLOGIES FOR SELF-EDUCATION AND SELF-DEVELOPMENT FOR ADULT PERSONALITY - Pichugina І.С. (Journal of Information Technologies in Education (ITE), 2015)
The use of information and communication technology for self-education and self-development of adults is becoming a pressing issue of our time. This article is intended to explore the current status of this issue, especially considering the growing importance of self-education of adults, the popularity of information and communication technologies in contemporary society, their application in various phases of public life and the life of an individual. An issue of modern educational environment is becoming an «education for life». Modern types of education, such as non-formal and informal, acquire development and allow an adult to undertake continuing education. An adult acquires a certain maturity as a person, but in modern society its further development becomes relevant for the reason that the needs and interests of society are changing rapidly. It makes a person also change rapidly through his / her self-development. Due to which people change their worldview, motivations, beliefs, personal characteristics, corrects a look at the meaning of his existence. The rapid and rapid development of information and communication technologies helps to relieve stress from modern reality. Their framework is based on a circulated network on the Internet, which opens a huge opportunity for any user and satisfies almost every informational request of a modern person. In the article we observed what options modern Internet environment offers for self-learning and self-development of an adult, and how these propositions may correspond the question posed